Gateway stability analysis by global-local modeling approach. (January 2019) - Basarir, Hakan; Sun, Yuantian; Li, Guichen
Abstract: Longwall mining is the most widely used mining method in underground coal mining. The stability of gateways is crucial for longwall mining as they provide many essential services such as transportation of excavated coal, ventilation of longwall face. High in situ stresses, mining induced stresses due to advancing longwall face, and poor rock mass quality leads to large deformation jeopardizing the stability of the gateway in Guobei coal mine. In this paper, the global-local modeling approach is used for analysing the stability of the gateway in the mine. In this approach, a mine scale 3D global model was constructed to extract the stresses acting on the gateway. The extracted stresses from global model were implemented into 2D local model of the gateway for detailed analysis. The used approach was verified by the field measurements taken from the modeled gateway. In an attempt to deal with large mine induced displacements, a support system composed of rock bolt, cable bolt and shotcrete was proposed. The verified model was used to evaluate the performance of proposed support system. It was concluded that the proposed support system can significantly reduce the displacements. The verified model facilitates the performance evolution of other alternative support systems considered by the mine management. The presented approach can be applicable for other deep underground coal mines, experiencing large gateway convergence.